Preparation and application of special liquid nitrile rubber and polyester resin
By grafting end-hydroxyl liquid nitrile rubber into polyester resin, the problem of poor impact performance of polyester resin under low temperature conditions is solved, the excellent toughness and low temperature performance of powder coatings are achieved, and its application scenarios are expanded and the development of green and environmentally friendly coatings is promoted.
Patent Information
- Application Number
- CN202411554566.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-28
AI Technical Summary
The existing polyester resins have poor toughness, especially the impact performance of powder coatings under low temperature conditions.
By grafting a special liquid nitrile rubber, especially a terminal hydroxyl liquid nitrile rubber, into a polyester resin structure, a polyester resin with excellent toughness and low temperature properties is prepared, and a powder coating made of the resin is made.
It improves the toughness of polyester resin and mechanical properties at low temperatures, especially impact properties, so that powder coatings can show excellent performance in a wider range of application scenarios, and promotes the development of green and environmentally friendly coatings.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of powder coatings, and in particular to a polyester resin prepared by using a special liquid nitrile rubber, a powder coating obtained by using the polyester resin, and a preparation method thereof. Background Art
[0002] Powder coatings have the 4E characteristics of efficiency, eco-friendliness, economy and excellence, and are widely used in seven fields: home appliances, furniture, building materials, 3C, general industry, engineering machinery and heavy anti-corrosion. Powder coatings have the environmental advantage of zero VOC, are healthier and more friendly to people and the environment, and have become one of the preferred coatings for green coatings.
[0003] With the expansion of the application fields of powder coatings, such as pipes, coils, and automotive springs, higher requirements are placed on the toughness of powder coatings, especially the performance at low temperatures. At present, the main method to improve the toughness of powder coatings is to introduce some raw materials with the effect of improving toughness into the formula for preparing powders, or to synthesize polyester resins with high toughness characteristics. Many patents disclose the preparation methods of high-toughness polyester resins, which are mainly achieved by introducing some long-chain synthetic monomers or polymers with special structures.
[0004] Liquid nitrile rubber is widely used in the toughening and modification of thermosetting resins such as epoxy resin, phenolic resin, BMI and CE. There are also a few patents disclosed for its direct application in powder coating formulations. However, there is no disclosure that it is grafted into the polyester resin structure to modify the toughness of the polyester resin and the resulting powder coating has excellent toughness and low-temperature performance. Summary of the invention
[0005] The present application provides a method for preparing a special liquid nitrile rubber and a polyester resin and a powder coating made from the polyester resin, so as to solve the technical problems in the prior art such as the poor toughness of the polyester resin and the poor impact performance of the powder coating under low temperature conditions.
[0006] In a first aspect, the present application provides a polyester resin, wherein the polyester resin is grafted with a liquid nitrile rubber, and the special liquid nitrile rubber is a hydroxyl-terminated liquid nitrile rubber;
[0007] The hydroxyl value of the hydroxyl-terminated liquid nitrile rubber is 10-20 mg KOH / g, and the bound acrylonitrile content is 20%-30%.
[0008] In an optional embodiment, the polyester resin includes the following raw materials, calculated in the following mass percentages: 30.0-40.0% diols, 0-5.0% polyols, 50.0-60.0% dibasic acids, 5.0-15.0% blocked acids, 3-8% special liquid nitrile rubber, 0.05-0.15% catalysts, 0.5-1.5% antioxidants, and 0.05-0.4% curing accelerators.
[0009] In a second aspect, the present application provides a method for preparing a polyester resin. The polyester resin described in any one embodiment of the first aspect is prepared by the following method:
[0010] S101. Add diol and polyol to a reaction kettle, heat to 80-100°C, then add polyacid and catalyst, and rapidly heat to 170-180°C under nitrogen atmosphere, generate and distill esterification water, heat to 240-245°C at a certain heating rate, and react at this temperature to clarify and take samples for testing;
[0011] S102, when the acid value reaches 15-30.0 mg KOH / g, lower the temperature to 210-220°C, add the end-capping acid, stir and slowly raise the temperature to 240°C, maintain the temperature at 235-245°C, react, clarify, and take samples for testing;
[0012] S103, when the acid value reaches 40-60 mg KOH / g, the temperature is maintained at 238-242° C., and the pressure in the kettle is slowly adjusted from normal pressure to negative pressure until the acid value reaches 35.0-48.0 mg KOH / g and then the temperature is lowered;
[0013] S104, when the temperature drops to 190-200°C, add special liquid nitrile rubber, catalyst and antioxidant, and keep warm for 1-2 hours;
[0014] S105, after the acid value reaches 30.0-45.0 mg KOH / g, adding a curing accelerator and an antioxidant, stirring and dispersing, cooling and discharging the material to obtain the polyester resin.
[0015] In an optional embodiment, the heating rate is 8 to 12° C. / h;
[0016] And / or, the negative pressure is -0.090 to -0.095 MPa, and the negative compression is performed for 3 to 5 hours.
[0017] In an optional embodiment, the special liquid nitrile rubber is prepared by the following method:
[0018] S201, adding an initiator, a solvent and a monomer into a kettle in sequence, and obtaining a liquid nitrile polymer by a free radical solution polymerization method;
[0019] S202, after washing, settling and separating the nitrile polymer, the rubber solution is sent to a dryer for drying, an antioxidant is added during the drying process, and the material is filtered out after drying to obtain the special liquid nitrile rubber.
[0020] In an optional embodiment, the monomers are butadiene and acrylonitrile;
[0021] And / or, based on 100 parts by mass of the monomers, the butadiene comprises 70 to 81 parts and the acrylonitrile comprises 19 to 30 parts.
[0022] In an optional embodiment, the initiator is hydrogen peroxide;
[0023] And / or, the concentration of the hydrogen peroxide is 30% to 32%;
[0024] And / or, the solvent is anhydrous ethanol.
[0025] In an optional embodiment, the mass ratio of the initiator to the monomer is 6 / 100 to 15 / 100;
[0026] And / or, the polymerization temperature is 100-120° C., and the reaction time is 3-5 hours.
[0027] In a third aspect, an embodiment of the present application provides a powder coating, wherein the raw materials of the coating include the polyester resin described in any one embodiment of the first aspect;
[0028] And / or, comprising a polyester resin prepared by the method described in any one of the embodiments of the second aspect.
[0029] In a fourth aspect, an embodiment of the present application provides a method for preparing a powder coating, wherein the powder coating as described in the third aspect is prepared by the following method:
[0030] The polyester resin, curing agent, titanium dioxide, barium sulfate, leveling agent and benzoin are uniformly mixed according to a certain proportion, and then melt-extruded and pressed into sheets;
[0031] After the flakes are cooled, they are crushed and sieved through a 200-500 mesh screen to obtain the powder coating.
[0032] Compared with the prior art, it also has the following beneficial effects:
[0033] The special liquid nitrile rubber of the present application is a terminal hydroxyl liquid nitrile rubber, which is grafted into the polyester resin structure to improve the toughness of the polyester resin, so that the prepared powder coating has excellent toughness, especially mechanical properties at low temperatures, such as impact resistance, which helps expand the application scenarios of powder coatings and promotes the development of green and environmentally friendly coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0035] Figure 1 A process flow chart of the preparation of polyester resin provided in the embodiments of the present application;
[0036] Figure 2 This is a flow chart of the preparation process of the special liquid nitrile rubber provided in the embodiments of the present application.
[0037] The above drawings have shown clear embodiments of the present application, which will be described in more detail later. These drawings and text descriptions are not intended to limit the scope of the present application in any way, but to illustrate the concept of the present application to those skilled in the art by referring to specific embodiments. DETAILED DESCRIPTION
[0038] Exemplary embodiments will be described in detail herein, examples of which are shown in the accompanying drawings. When the following description refers to the drawings, the same numbers in different drawings represent the same or similar elements unless otherwise indicated. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application. Instead, they are merely examples of devices and methods consistent with some aspects of the present application as detailed in the appended claims.
[0039] The technical solution of the present application and how the technical solution of the present application solves the above-mentioned technical problems are described in detail below with specific embodiments. The following specific embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The embodiments of the present application will be described below in conjunction with the accompanying drawings.
[0040] According to Figure 2 The preparation process flow is to prepare liquid nitrile rubber. The specific raw materials and preparation temperature, as well as the test indicators are shown in Table 1. Figure 1 The polyester resin is prepared by the preparation process, and the specific raw materials, preparation temperature, and detection indicators are shown in Table 2.
[0041] Table 1 Synthetic special liquid nitrile rubber and its indicators
[0042]
[0043]
[0044] The hydroxyl value is determined by chemical titration, specifically according to 4.4.3 of GJB 1327A-2021. The test method is as follows: Weigh 1.3 grams of sample (accurate to 0.0001), place it in a 250mL iodine volumetric flask, add 5.00ml of acylating agent, and use a rubber ring to tighten the bottle stopper. After the sample is completely dissolved, place it in a (50±1)℃ constant temperature water bath and heat it for 30 minutes with frequent shaking. After cooling, add 2mL of water to mix it thoroughly, then add 2mL of pyridine solution, cover the bottle stopper, place it in the above constant temperature water bath, and heat it for 10 minutes with frequent shaking until the reaction is complete. After cooling, add 25mL of benzene and 5 drops of phenolphthalein indicator, and titrate with 0.1mol / L potassium hydroxide-ethanol standard solution until a slightly reddish color appears. The end point is that it does not disappear for 30 seconds. The hydroxyl value is then calculated according to the formula.
[0045] The combined nitrile content is tested according to the method specified in Appendix E of GJB 2050A-2020. The test method is: using an elemental analyzer, weigh 3-5 mg of the sample into a solid sample pool, put it into the sample tray, test it according to the procedure, and calculate the combined nitrile content according to the timely formula.
[0046] The synthesis and index test results of the liquid nitrile rubber embodiment and comparative example are shown in Table 1. HTBN-A, HTBN-B and HTBN-C are special liquid nitrile rubbers provided by the present application, hydroxyl-terminated liquid nitrile rubbers with a hydroxyl value of 10-20 mg KOH / g and a combined acrylonitrile content of 20-30%, while HTBN-1 is a liquid nitrile rubber with a hydroxyl value of <10 mg KOH / g and a combined acrylonitrile content of <10%, and HTBN-2 is a liquid nitrile rubber with a hydroxyl value of >30 mg KOH / g and a combined acrylonitrile content of >30%.
[0047] Table 2. Synthetic polyester resin and its indexes
[0048]
[0049]
[0050] The acid value test of polyester resin is carried out in accordance with the standard of GB / T 6743-2008. The test method is as follows: weigh 1.0 g of sample (accurate to 0.001), place it in a 250 ml stoppered conical flask, add 50 ml of mixed solution (90% tetrahydrofuran: 10% water), shake it well to make it completely dissolved, then add 5 drops of phenolphthalein indicator, and titrate it with 0.1 mol / L potassium hydroxide standard solution until the reddish color does not disappear, and then calculate the acid value according to the formula.
[0051] The melt rotation viscosity test of the resin is carried out in accordance with the standard GB / T 9751.1-2008. The test method is as follows: take 0.095-0.105 grams of sample and put it on the test surface of the viscometer. When the sample melts and the bubbles are gone, press the pressure rod. After the temperature stabilizes at the set temperature, press the RUN button to start the test. After the test is completed, read the data.
[0052] The glass transition temperature of the resin is determined according to the standard of GB / T 19466.2-2004. The test method is as follows: using a differential scanning calorimeter to test, weighing 7 to 10 mg of the sample, a nitrogen flow rate of 20 mL / min, heating from 0°C to 100°C at a heating rate of 10°C / min, and taking the Tg value of the second heating curve.
[0053] The test results of the embodiments and comparative examples are shown in Table 2. It can be seen from Table 2 that the addition of the special liquid nitrile rubber provided in the present application will reduce the viscosity and glass transition temperature (Tg) of the polyester resin, especially the Tg of polyester PE-② is only 53.14°C, which is 10°C lower than that of polyester PE-a. However, too low Tg affects the storage stability of the polyester resin, and it is easy to agglomerate at high temperature, thereby affecting the preparation and storage of powder coatings, which is limited in practical applications.
[0054] Table 3. Preparation of powder coatings and their indicators
[0055]
[0056]
[0057] Powder coating film performance test standards:
[0058] The coating thickness test is carried out in accordance with the standard GB / T 13452.2-2008. The test method is: take measurements at different positions not less than 1 cm from the edge of the sample. Place the probe on the sample and press the button to read the coating thickness value.
[0059] The gloss test of the film is carried out in accordance with the standard GB / T 1743-1979. The test method is as follows: first, wipe the surface of the sample to be measured clean, then place the instrument test port on the part to be tested on the sample, and the value displayed on the instrument is the gloss value of that part.
[0060] The impact performance test of the coating is carried out in accordance with the standard of GB / T 1732-1993. The test method is as follows: place the sample on the iron felt, fix the weight on the slide at a height of 100cm or 50cm, press the control knob, and the weight will fall freely on the punch. Record the coating thickness and the surface condition of the coating after impact.
[0061] The polyester resin PE synthesized in this application is weighed and mixed with TGIC, titanium dioxide, barium sulfate, benzoin, leveling agent (588), brightener (701B) in the same proportion according to Table 3, and then melted, extruded, tableted, and crushed by a screw extruder, and then the tablets are crushed and sieved to make powder coatings. The powder coating is sprayed on a surface treated (phosphating) metal plate with an electrostatic spray gun, cured at 200℃ / 10min, and then the performance test is carried out. Among them, the impact performance is tested at room temperature (25℃) and low temperature (-0℃), and the sample is placed for 48h. The performance test results are shown in Table 3.
[0062] As can be seen from Table 3, the powder coating prepared by grafting the polyester resin with the special liquid nitrile rubber (hydroxyl value 10-20 mg KOH / g, combined with acrylonitrile content 20-30%) provided by the present application has excellent impact properties at room temperature, especially at low temperatures. Compared with no addition of liquid nitrile modified It has good impact properties, but the Tg of its polyester resin PE-② is too low, only 53.14℃. The polyester resin is easy to agglomerate during storage and easy to stick during processing, which affects the manufacture and storage of powder coatings and is difficult to implement in practical applications.
[0063] In the above embodiments, the description of each embodiment has its own emphasis. For parts not described in detail in a certain embodiment, please refer to the relevant description of other embodiments. The technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0064] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the invention disclosed herein. The present application is intended to cover any modification, use or adaptation of the present application, which follows the general principles of the present application and includes common knowledge or customary techniques in the art that are not disclosed in the present application. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present application are indicated by the following claims.
[0065] It should be understood that the present application is not limited to the precise structures that have been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof. The scope of the present application is limited only by the appended claims.
Claims
1. A polyester resin, characterized in that The polyester resin is grafted with a special liquid nitrile rubber, and the liquid nitrile rubber is a hydroxyl-terminated liquid nitrile rubber; The hydroxyl value of the hydroxyl-terminated liquid nitrile rubber is 10-20 mg KOH / g, and the bound acrylonitrile content is 20%-30%.
2. The polyester resin according to claim 1, characterized in that According to the following mass percentages, the polyester resin includes the following raw materials: 30.0-40.0% diol, 0-5.0% polyol, 50.0-60.0% dibasic acid, 5.0-15.0% blocked acid, 3-8% special liquid nitrile rubber, 0.05-0.15% catalyst, 0.5-1.5% antioxidant, and 0.05-0.4% curing accelerator.
3. A method for preparing a polyester resin, characterized in that: The polyester resin as claimed in claim 1 or 2 is prepared by the following method: S101. Add diol and polyol to a reaction kettle, heat to 80-100°C, then add polyacid and catalyst, and rapidly heat to 170-180°C under nitrogen atmosphere, generate and distill esterification water, heat to 240-245°C at a certain heating rate, and react at this temperature to clarify and take samples for testing; S102, when the acid value reaches 15-30.0 mg KOH / g, lower the temperature to 210-220°C, add the end-capping acid, stir and slowly raise the temperature to 240°C, maintain the temperature at 235-245°C, react, clarify, and take samples for testing; S103, when the acid value reaches 40-60 mg KOH / g, the temperature is maintained at 238-242° C., and the pressure in the kettle is slowly adjusted from normal pressure to negative pressure until the acid value reaches 35.0-48.0 mg KOH / g and then the temperature is lowered; S104, when the temperature drops to 190-200°C, add special liquid nitrile rubber, catalyst and antioxidant, and keep warm for 1-2 hours; S105, after the acid value reaches 30.0-45.0 mg KOH / g, adding a curing accelerator and an antioxidant, stirring and dispersing, cooling and discharging the material to obtain the polyester resin.
4. The preparation method according to claim 3, characterized in that: The heating rate is 8-12°C / h; And / or, the negative pressure is -0.090 to -0.095 MPa, and the negative compression is performed for 3 to 5 hours.
5. The preparation method according to claim 3, characterized in that: The special liquid nitrile rubber is prepared by the following method: S201, adding an initiator, a solvent and a monomer into a kettle in sequence, and obtaining a liquid nitrile polymer by a free radical solution polymerization method; S202, after washing, settling and separating the nitrile polymer, the rubber solution is sent to a dryer for drying, an antioxidant is added during the drying process, and the material is filtered out after drying to obtain the special liquid nitrile rubber.
6. The preparation method according to claim 5, characterized in that: The monomers are butadiene and acrylonitrile; And / or, based on 100 parts by mass of the monomers, the butadiene comprises 70 to 81 parts and the acrylonitrile comprises 19 to 30 parts.
7. The preparation method according to claim 5, characterized in that: The initiator is hydrogen peroxide; And / or, the concentration of the hydrogen peroxide is 30% to 32%; And / or, the solvent is anhydrous ethanol.
8. The preparation method according to claim 5, characterized in that: The mass ratio of the initiator to the monomer is 6 / 100 to 15 / 100; And / or, the polymerization temperature is 100-120° C., and the reaction time is 3-5 hours.
9. A powder coating, characterized in that: The raw materials of the coating include the polyester resin according to claim 1 or 2; And / or, comprising a polyester resin prepared by the method according to any one of claims 2 to 8.
10. A method for preparing a powder coating, characterized in that: The powder coating according to claim 9 is prepared by the following method: The polyester resin, curing agent, titanium dioxide, barium sulfate, leveling agent and benzoin are uniformly mixed according to a certain proportion, and then melt-extruded and pressed into sheets; After the flakes are cooled, they are crushed and sieved through a 200-500 mesh screen to obtain the powder coating.